Quantitative method for normalization of transfection efficiency using enhanced green fluorescent protein - Dandekar, D. H.; Kumar, M.; Ladha, J. S.; Ganesh, Krishna N.; Mitra, Debashis (Analytical Biochemistry, 2005)

Amino functionalized novel cholic acid derivatives induce HIV-1 replication and syncytia formation in T cells - Salunke, Deepak B.; Ravi, D. S.; Pore, V. S.; Mitra, Debashis; Hazra, Braja G. (Journal of Medicinal Chemistry, 2006)
Synthesis of C-11 azido/amino functionalized cholic acid derivatives has been achieved in excellent yields. Contrary to the previous prediction of analogous compounds to be HIV-1 protease inhibitors, in the present study these novel cholic acid derivatives induced host cell fusion during the progress of HIV-1 infection and produced multinucleated giant cells. This is the first report of syncytia induction and enhancement of viral replication in HIV-1 infected T cells by cholic acid derivatives.

Design, synthesis, docking studies and biological screening of 2-thiazolyl substituted-2,3-dihydro-1H-naphtho[1,2-e][1,3]oxazines as potent HIV-1 reverse transcriptase inhibitors - Gawali, Rakhi; Trivedi, Jay; Bhansali, Sujit; Bhosale, Raghunath; Sarkar, Dhiman; Mitra, Debashis (European Journal of Medicinal Chemistry, 2018)
1,3-oxazine nucleus and thiazolyl group features prominently in many biologically important natural products as well as bioactive molecules. A series of novel 2-thiazolyl substituted-2,3-dihydro-1H-naphtho [1,2-e][1,3]oxazine derivatives were designed and synthesized based on their structure-activity relationships (SARs) from 2-naphthol, substituted thiazolyl amines and formalin through ring closure by one-pot three component reaction. These derivatives were first evaluated for their inhibitory effect on HIV-1 Reverse Transcriptase (RT) enzyme activity. Out of 14 compounds, 4 showed potent inhibition of HIV-1 RT activity at significantly low concentration. Docking studies of these molecules revealed their high affinity binding to several amino acids of HIV-1 RT which are less sensitive to point mutations. Furthermore, anti-HIV activity of these molecules was analysed in a CD4(+) T cell-line, which indicates that Therapeutic Index (TI) of some of these compounds is better than Zidovudine and Efavirenz, known HIV-1 RT inhibitors. Taken together, our studies report for the first time some novel naphthoxazine derivatives with significant TI, which is through inhibition of HIV-1 RT activity. (C) 2018 Elsevier Masson SAS. All rights reserved.